2018
DOI: 10.1016/j.appet.2018.05.139
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical activity, appetite and energy intake in older adults: A systematic review

Abstract: Ageing often causes a reduction in appetite and energy intake in older adults which can result in malnutrition. Current guidelines for older adults suggest increasing physical activity to enhance appetite. However, it is unclear if there is evidence to support this advice. This aim of this review is to assess if appetite and energy intake is changed in older adults that undertake acute or regular physical activity (measured from cross sectional and intervention studies). Databases SPORTDiscus, CINAHL, MEDLINE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…In addition, the energy cost of running can be expected to be higher for older runners (Pantoja et al, 2016). Participating in physical activity is thought to increase appetite, reducing the risk of the anorexia of ageing; however, a recent systematic review concluded that there is insufficient evidence to apply this statement to older adults (Clegg and Godfrey, 2018). This is supported by our findings: reduced energy intake in the current study was significantly associated with age, suggesting that an active lifestyle may not be sufficient to moderate reduction in appetite associated with ageing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the energy cost of running can be expected to be higher for older runners (Pantoja et al, 2016). Participating in physical activity is thought to increase appetite, reducing the risk of the anorexia of ageing; however, a recent systematic review concluded that there is insufficient evidence to apply this statement to older adults (Clegg and Godfrey, 2018). This is supported by our findings: reduced energy intake in the current study was significantly associated with age, suggesting that an active lifestyle may not be sufficient to moderate reduction in appetite associated with ageing.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the relationships between exercise, physical activity, and appetite are poorly researched in older adults, with a marked paucity of aging-specific data (13,17,30). Previous research (3,9,13,17,21,22,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) on the effects of exercise and physical activity on appetite in aging populations is inconsistent and appears to be unclear. The purpose of this systematic review and meta-analysis was to assess the existing literature on exercise and physical activity interventions in older adult populations, with the aim of better understanding how they may impact hunger and satiety in aging groups.…”
Section: Introductionmentioning
confidence: 99%
“…These anabolic effects are well studied for animal protein (Boirie & Guillet, 2018), but little is known about the effects of plant proteins on digestion and protein metabolism. Physical activity also enhances energy expenditure and may increase appetite in some circumstances, but evidence for this in older adults and an understanding of underlying mechanisms is currently very limited (Clegg & Godfrey, 2018;Grannell et al, 2019).…”
Section: Introductionmentioning
confidence: 99%